Consumer's fairness: Substantive and procedural legal aspects - A.N. Kuzbagarov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The problem of unfair behavior demonstrated by the consumer in contractual relations has been considered in the paper. It has been shown how to ensure the principle of inadmissibility of dishonesty which is enshrined in Art. 1 of the Civil Code of the Russian Federation (as amended in the Federal Law no. 302-FL on December 30, 2012) has taken effect since March 1, 2013. The examples from the legal practice proving that no legal treatment is often given to such behavior during the administration of justice have been provided. Nevertheless, the existence of a burden of conscientious behavior of the consumer in the civil legislation of the Russian Federation has been proved. In case of derogation from it, the norms of substantive and procedural law in the form of sanctions must be applied to the consumer. This approach, according to the author, will balance the rights and obligations of the parties of the contractual relation and level so-called consumer extremism.